Navigating hospital foodservice satisfaction: Insights from Importance-Performance Map Analysis - Felicia Setiawan; Ferdi Antonio; Renate Parlene Marsaulina; Valencia Hadinata; Arif Laksono Utomo; Claudia Alexandra; Rizky Ramadhana; Catharina Catharina (AcTion: Aceh Nutrition Journal, 2024)
Hospital food service satisfaction is critical to inpatient care quality and affects patients’ experiences and well-being. This study employed Importance-Performance Map Analysis (IPMA) to systematically evaluate and enhance food service satisfaction in inpatient care within healthcare facilities. A cross-sectional quantitative survey was conducted in August 2023 at a 300-bed private hospital in Central Jakarta involving 324 conscious patients aged > 17 years. The Acute Care Hospital Foodservice Patient Satisfaction Questionnaire (ACHFPSQ) was used to measure various food service factors. IPMA analysis has illuminated a strategic path for healthcare institutions to enhance food service satisfaction. IPMA analysis showed that Meal Taste, Meal Portion, and Meal Serving were highly important and performed well. These aspects should be maintained to ensure satisfaction with food services. Meal Variety and Utensils were identified as areas of high importance but low performance, warranting improvement. By acknowledging the strengths (meal taste, meal portion, and meal serving) and weaknesses (meal variety and utensils) of various food service components and prioritizing improvements accordingly, hospitals can better cater to the preferences and needs of their inpatient population, ultimately leading to increased satisfaction and improved overall healthcare experience.